Smartphone use and mental health - findings from a 30-day longitudinal study among young talented volleyball players - Hilpisch, C.; Zentgraf, K.; Mutz, M. (International Journal of Sport and Exercise Psychology, 2025)
This longitudinal study examines the impact of smartphone use on mental health-related outcomes in a sample of N = 47 of Germany's most talented young male volleyball players. Accounting for both inter- and intra-individual variation in smartphone use, we investigate the coexistence and impact of three temporally distinct effects: habitual, short-term, and late-night smartphone use. Results highlight the consequences of habitual effects, with higher levels of regular smartphone use being associated with increased symptoms of anxiety, depression, and sleep complaints. In addition, we find negative non-linear relationships between habitual smartphone use and athletes' emotional well-being and concentration during training. In terms of short-term effects, athletes report more mind-wandering during training sessions following days of higher smartphone use, while no evidence is found for the hypothesised late-night effect. We conclude that habitual smartphone use exceeding approximately 4 hours a day is problematic for young athletes' performance and mental health. Athletes, coaches, and sport psychologists should be made aware of the importance of managing screen time.